Model Bisnis Fintech Syariah dalam Mendukung Pengembangan UMKM Halal: Studi Kasus ALAMI Fintech Syariah - Chanda Nur Margareta (ARTHASASTRA : Journal of Economics and Business, 2026)
The rapid digital transformation in the financial sector has accelerated the development of Islamic fintech as an inclusive financing alternative for halal-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, studies examining Islamic fintech business models integrated with the principles of maqāṣid al-syarī‘ah in supporting halal MSMEs remain limited. This study aims to analyze the Islamic fintech business model in supporting the development of halal MSMEs through a case study of ALAMI Islamic Fintech. This research employs a descriptive qualitative method using literature review and case study approaches. Data were collected from scientific journals, reports published by the Financial Services Authority (OJK), Bank Indonesia publications, and official sources from Islamic fintech companies. Data analysis was conducted through data reduction, data presentation, and descriptive-analytical conclusion drawing. The findings indicate that the Islamic fintech business model plays a significant role in expanding access to halal financing, improving Islamic financial inclusion and literacy, and strengthening the real sector of MSMEs through sharia-based financing contracts such as mudharabah, murabahah, and wakalah bil ujrah. The case study of ALAMI Islamic Fintech demonstrates that the implementation of maqāṣid al-syarī‘ah principles in a peer-to-peer lending system is capable of creating a balance between profitability, transparency, social justice, and business sustainability. This study contributes to the development of Islamic fintech business model studies based on Islamic values in supporting the halal economic ecosystem in the digital era.